AN OVERVIEW OF SQUATTER SETTLEMENTS IN ADDIS ABABA, ETHIOPIA (Journal of Governance and Development (JGD), 2021)
Squatter/informal settlements are notable features of the urban areas of developing counties. This study aims at exploring the facts related to squat settlements in Ethiopia, with reference to the capital city, Addis Ababa. The study tries to explore the causes, scale and consequences of squatter settlements. It also attempts to assess municipal responses aimed at redressing the problems evolving from the proliferation of squatter settlements within and the suburbs of the city. The study is based on secondary data available to demonstrate the spread and challenges brought about by informal settlements. Related literature is reviewed to provide theoretical background. The emergence and alarming increase of squatter settlements has been caused by multiple factors, including the delays in the implementation of legal land provisions for housing and escalating costs of owning formal houses. The growth of slums and squatter settlements has been among the key urban planning and management hurdles for the city. The city government adopted preventive and curative measures to deter the emergence and prevalence of squatter settlements. The approaches range from demolition of “non-poverty-driven” to regularization of “poverty-driven” informal settlements. However, squatter settlementshave continued to proliferate despite the successive regulatory measures taken by the concerned government organs. This trend is due mainly to unrestrained poverty and population pressure complemented with weak municipal capacity to handle the problem.